Πρώιμη ιστορική μαρτυρία για τις Κυδωνίες (1653) - Πατρινέλης Χρήστος Γ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1993)
Kydonies or Aivali became widely known as one of the most important educational and commercial centres in the Greek East in the first years of the nineteenth century. However, apart from some vague oral traditions, almost nothing certain was known about the earlier history of the town. In the present study I edit and comment on a document dated 1653, and preserved in Cod. Hierosolymitanus 509. It is a list of names of inhabitants of Kydonies who had offered monetary contributions for the Orthodox Patriarchate of Jerusalem. The list consists of 33 entries (corresponding to family units) in which 173 Christian and family names are mentioned. On the basis of this material, and in correlation with similar entries of the codex from other communities of the area, we may conclude that Kydonies had been a well established village of considerable size by 1653. Its population consisted of immigrants from the island of Lesbos mainly, but also from Chios as well as from neighbouring Greek communities of Western Asia Minor, and —in a lesser percentage— from Greece proper.